2012
DOI: 10.1021/jf300749r
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Malt Roasting on the Oxidative Stability of Sweet Wort

Abstract: Influence of malt roasting on the oxidative stability of sweet wort was evaluated based on radical intensity, volatile profile, content of transition metals (Fe and Cu) and thiols. Malt roasting had a large influence on the oxidative stability of sweet wort. Light sweet worts were more stable with low radical intensity, low Fe content, and ability to retain volatile compounds when heated. At mild roasting, the Fe content in the wort increased but remained close to constant with further roasting. Dark sweet wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 26 publications
8
39
1
Order By: Relevance
“…The colour of wort made from pilsner malt was not affected by storage time and conditions. The pH of the worts was constant throughout the experiment, and generally the pH of the pilsner wort was approximately one unit higher than that of the wort made from roasted malt, in line with previous findings . The sugar content was also constant throughout the 12 months of storage for both types of worts.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The colour of wort made from pilsner malt was not affected by storage time and conditions. The pH of the worts was constant throughout the experiment, and generally the pH of the pilsner wort was approximately one unit higher than that of the wort made from roasted malt, in line with previous findings . The sugar content was also constant throughout the 12 months of storage for both types of worts.…”
Section: Resultssupporting
confidence: 89%
“…Selected volatiles were studied in relation to storage and it was observed that Strecker aldehydes and N ‐heterocyclic compounds increased slightly in concentration within the first few months and then decreased to concentrations below the initial content, and interestingly similar variations in malt and beer aromas were identified . In a recent study it was found that sweet worts made from roasted malts with colours above 33 EBC units were very susceptible to a loss of volatiles when exposed to mild heating, whereas the profile of volatile compounds of wort made from pilsner malt was not affected by the heating .…”
Section: Introductionmentioning
confidence: 99%
“…The increasing intensity of the pink colour suggests an increase of hydroperoxide groups in malts kilned to a higher degree. This data is supported by current research that shows an increase in organic radicals and a decrease in oxidative stability in worts produced by dark specialty malts .…”
Section: Resultssupporting
confidence: 83%
“…The sample of boiled wort was collected after 30 min of boiling, immediately before hops were added, and the sample of hopped boiled wort was collected after 90 min of boiling, immediately before cooling. Sweet wort was found to have the lowest radical forming intensity compared with boiled wort and hopped boiled wort in line with previous studies (6,17).…”
Section: Wort and Beersupporting
confidence: 90%